Towards Meaningful Biology Learning: A Needs Analysis for Developing a Deep Learning–Project-Based E-Module - Annisa Aulia; Sudarmin; Novi Ratna Dewi (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The increasing complexity of biological concepts and the growing demand for twenty-first-century competencies require innovative learning resources that support both conceptual understanding and collaborative learning. This study aimed to analyze the needs of teachers and students regarding the development of a Biology e-module integrating Deep Learning and Project-Based Learning (DL-PjBL). A descriptive mixed-methods design was employed within the Analysis phase of the ADDIE framework. Participants consisted of 30 senior high school students and one Biology teacher selected through convenience sampling. Data were collected using a student needs questionnaire, classroom observations, and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The findings revealed a strong need for innovative digital learning materials, with 93.3% of students expressing the need for interactive e-modules and 83.3% reporting difficulties in understanding abstract Biology concepts. Furthermore, classroom observations indicated limited collaborative interaction, fragmented conceptual understanding, and a predominance of teacher-centered learning practices. Interview findings confirmed the need for learning resources that combine authentic project activities with reflective and meaningful learning experiences. The convergence of quantitative and qualitative findings suggests that a DL-PjBL-based Biology e-module has substantial potential to address existing pedagogical challenges by fostering collaboration and facilitating deeper conceptual understanding. This study provides an empirical foundation for the subsequent design and development of digital instructional materials that align with contemporary educational demands and support meaningful Biology learning.